The Inuit Qaujimajatuqangit Health System: A Holistic, Strength-based, and Health-promoting Model from and for Inuit Communities - Healey Akearok, Gwen; Mearns, Ceporah; Mike, Nancy (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2023)
Public health models are important frameworks for guiding public health action. Although numerous public health models are found in the literature, a dearth of models focus on the health paradigms of Indigenous communities, globally, yet no models are derived from Inuit health perspectives and knowledge. Inuit Qaujimajatuqangit is an all-encompassing term that refers to Inuit knowledge and practices across time. Using a mixed-method, narrative analysis approach, the Inuit Qaujimajatuqangit Health System Model has emerged as a holistic, trauma- and resilience-informed, strength-based, and community-grounded public health model. This model can serve as a guide for systems change as well as public health interventions, health programs, clinical services, patient-oriented research, health human-resource modeling, and health policy for Inuit communities.